Pengaruh Konten Vlog YouTube Rans Entertainment terhadap Persepsi Penonton pada Brand Luxury - Roni Maulana; Nyoman Puspadarmadja (Bandung Conference Series: Journalism, 2023)
Abstract. This study aims to determine the impact of RANS Entertainment's YouTube vlog content on audience perceptions of luxury brands. Along with the development of technology and the increasing use of social media, especially YouTube, public figures are competing to create content to attract attention and make money. One of the most popular YouTube content is Raffi Ahmad's YouTube vlog content which is managed by the RANS Entertainment production house. Each content always displays their daily lifestyle. The theory used in this research is para-social interaction theory, and YouTube vlog content is measured by three dimensions, namely social attractiveness, physical attractiveness, and para-social interaction. Furthermore, the variable of audience perception on luxury brands is measured by three dimensions, namely brand value, brand-user imagery fit, and luxury brands. The research uses quantitative methods and survey methods with questionnaires. The research sample consisted of 80 participants. A basic linear regression formula was used to test hypotheses. The results demonstrated that RANS Entertainment's YouTube Vlog material had a significant impact on the viewers' perceptions of luxury brands within the moderate influence category. This means that the more RANS Entertainment's YouTube vlog content is improved, the audience's perception of luxury brands will increase. Abstrak. Penelitian ini bertujuan untuk mengetahui dampak konten vlog YouTube RANS Entertainment terhadap persepsi penonton pada brand luxury. Seiring kemajuan teknologi dan meningkatnya penggunaan media sosial, khususnya YouTube, membuat para publik figure berlomba-lomba membuat konten untuk mendapatkan perhatian dan menghasilkan uang. Salah satu konten YouTube yang paling digemari adalah konten vlog YouTube milik Raffi Ahmad yang dikelola oleh rumah produksi RANS Entertainment. Di setiap kontennya selalu menampilkan gaya hidup mereka sehari-harinya. Teori yang digunakan dalam penelitian ini adalah teori para-social interaction. Konten vlog YouTube diukur dalam tiga dimensi yakni daya tarik sosial, daya tarik fisik, dan interaksi para-sosial. Selanjutnya, variabel persepsi penonton pada brand luxury diukur dengan tiga dimensi: brand value, brand-user imagery fit, dan brand luxury. Penelitian menggunakan metode kuantitatif dan metode survei dengan kuesioner. Sampel penelitian sebanyak 80 orang. Pengujian hipotesis menggunakan rumus regresi linear sederhana. Hasil penelitian menunjukkan bahwa konten vlog YouTube RANS Entertainment memberikan dampak terhadap persepsi penonton pada brand luxury, yang signifikan dalam kategori pengaruh sedang. Artinya, semakin banyak konten vlog YouTube RANS Entertainment yang ditingkatkan, maka persepsi penonton pada brand luxury akan meningkat.